The Virtue of Just Enough Stress: A Molecular Model - Bishopric, Nanette H. (American Clinical and Climatological Association, 2012)
Molecular biology emphasizes the study of all-or-nothing phenomena and molecular events with a large dynamic range. However, many important physiologic parameters in the clinical setting are tightly constrained (e.g., serum sodium concentration, body mass, venous oxygen saturation, sleep duration). Stress responses exhibit both a wide dynamic range and a potential for important effects at a “just-enough” threshold activation level. Stress responses occur in a number of body systems (e.g., neuropsychiatric, immune, cardiovascular) and are essential for short-term damage control, but also must be tightly constrained in range and duration to permit the organism to walk the narrow homeostatic path to long-term survival. Using an example of a newly appreciated stress-responsive molecule in the heart, acetyltransferase p300, as well as examples from the literature, this article discusses the advantages of self-limited stress, the adverse effects of sustained stress, and the built-in mechanisms that feed back on and terminate stress signals, and advances a hypothesis regarding stress as a pharmacological target in the heart.